Skin microbiota during metamorphosis of Quasipaa spinosa: guidance for maintaining mucosal symbiotic microbial flora homeostasis in early life of frogs - Jinliang Hou; Yu Tan; Yanfei Huang; Hong Li; Deliang Li; Xinhua Liu; Junhua Li; Yazhou Hu; Jianguo Xiang (Frontiers in Microbiology)
The skin microbiota plays an essential role in helping the host adapt to different environments and maintain health. By examining the characteristics of amphibian skin flora alongside ontogenetic traits, we can gain insights into the adaptation mechanisms of amphibian skin flora to environmental changes during development. In this study, we analyzed the skin microbiota of Quasipaa spinosa during metamorphosis using Illumina sequencing. Venn diagrams and UpSet analysis revealed that the LTS (hindlimb tadpoles’ skin, aquatic habitat) and FTS (forelimb tadpoles’ skin, shift from aquatic to amphibious habitats) groups exhibited a higher number of unique amplicon sequence variants (ASVs), while the TS (tadpoles’ skin, aquatic habitat) and LFS (land frogs’ skin, amphibious habitats) groups displayed a lower abundance of ASVs. Diversity analysis indicated similarities in the microorganisms between the LTS and the FTS groups, with higher microbial diversity compared to the TS and the LFS groups. Additionally, microbial co-occurrence network analysis indicated a more stable microecology in the LTS group and FTS group. Proteobacteria, Firmicutes, and Bacteroidota were identified as the dominant phyla, although their relative abundances varied widely among groups. LEfSe (Linear discriminant analysis effect size) showed significant enrichment of beneficial bacteria at various developmental stages, including Bacteroides, Bacillus, and Lactobacillus. Functional prediction analysis shows significant differences in skin microorganism functions across various developmental stages, with a primary focus on metabolic functions. This study provides valuable insights into the compositional dynamics of skin microbiota in Q. spinosa at various developmental stages.